Applying Lean Techniques to Reduce Intravenous Waste Through Premixed Solutions and Increasing Production Frequency. Issue 1 (January 2018) - Lin, Alex C.; Penm, Jonathan; Ivey, Marianne F.; Deng, Yihong; Commins, Monica
Abstract : Background: This study aims to use lean techniques and evaluate the impact of increasing the use of premixed IV solutions and increased IV production frequency on IV waste. Methods: Study was conducted at a tertiary hospital pharmacy department in three phases. Phase I included evaluation of IV waste when IV production occurred three times a day and eight premixed IV products were used. Phase II increased the number of premixed IV products to 16. Phase III then increased IV production to five times a day. Results: During Phase I, an estimate of 2, 673 IV doses were wasted monthly, accounting for 6.14% of overall IV doses. This accounted for 688 L that cost 60, 135. During Phase II, the average monthly IV wastage reduced significantly to 1, 069 doses (2.84%), accounting for 447 L and 34, 003. During Phase III, the average monthly IV wastage was further decreased to 675 doses (1.69%), accounting for 78 L and 3, 431. Hence, a potential annual saving of 449, 208 could result from these changes. Conclusion: IV waste was reduced through the increased use of premixed solutions and increasing IV production frequency.